(untitled) (Bangladesh Medical Journal, 2011)
Key words: perception; educational environment; academic achiever; academic under-achiever; medical college DOI: 10.3329/bmj.v39i2.7029 Bangladesh Medical Journal 2010, 39(2) pp.2-10